Discussion on 'relaxation method for pounding action between adjacent buildings at expansion joint' by H. Takabatake, M. Yasui, Y. Nakagawa and A. Kishida. (3rd November 2014) - Khatiwada, Sushil; Chouw, Nawawi; Larkin, Tam
SUMMARY The paper under discussion presents a detailed study on the reduction of pounding force on buildings due to expansion joints being filled with rubber. From shake table experiments and numerical simulations, the authors of the paper concluded that the rubber can reduce the maximum pounding force and hence the pounding damage to buildings. However, the writers of this short communication observed some significant issues in the experimental results as well as the numerical simulations. These observations are presented and raise questions about the validity of the results and the subsequent conclusions. Copyright © 2014 John Wiley & Sons, Ltd.